Natural Silicate-Tio2 Hybrids for Photocatalytic Oxidation of Formaldehyde in Gas Phase - Villarroel-Jorquera, M; Villarroel-Jorquera, M (ELSEVIER SCIENCE SA, 2017)
Structured hybrid materials based on the combination adsorbent-photocatalyst with optimal mechanical resistance and reduced cost, are prepared by extrusion using four different natural silicates with similar mesoporous distribution: sepiolite (S), bentonite (B), mordenite (M) and kaolinite (K). The effect of the textural, morphological and structural properties of plate shaped composites calcined at different temperatures on the adsorption and photocatalytic degradation of formaldehyde in gas phase is analyzed. Silicates allows TiO2 extrusion into flat plates with a content of 50 wt% of titania. All shaped materials present adequate mechanical resistance to be scaled-up for use in continuous-flow gas-phase catalytic reactors. Thermal treatment at 500 degrees C ensures an optimum combination of mechanical, textural and HCHO adsorption properties. The silicates cover part of the TiO2 particles thus reducing the fraction of TiO2 actually exposed on the surface of the composites, essential to carried out the photocatalytic process, but they also allow controlling TiO2 dispersion and the amount of HCHO adsorbed. The HCHO degradation rate is enhanced with all the silicate-TiO2 composites with respect to that of the benchmark TiO2. The incorporation of titania into the silicate matrix favors the gas phase removal of HCHO in the following sequence: MTi > KTi > STi > BTi > TiO2. The exposed fraction of titania particles and the size of the TiO2 anatase crystalline domains determine the efficiency of the hybrid material, which is optimized in high-aluminum kaolinite and mordenite based hybrids. (C) 2016 Elsevier B.V. All rights reserved.